Attenuated BMP1 Function Compromises Osteogenesis, Leading to Bone Fragility in Humans and Zebrafish - Asharani, P.V. (Elsevier, 2012)
Bone morphogenetic protein 1 (BMP1) is an astacin metalloprotease with important cellular functions and diverse substrates, including extracellular-matrix proteins and antagonists of some TGFβ superfamily members. Combining whole-exome sequencing and filtering for homozygous stretches of identified variants, we found a homozygous causative BMP1 mutation, c.34G>C, in a consanguineous family affected by increased bone mineral density and multiple recurrent fractures. The mutation is located within the BMP1 signal peptide and leads to impaired secretion and an alteration in posttranslational modification. We also characterize a zebrafish bone mutant harboring lesions in bmp1a, demonstrating conservation of BMP1 function in osteogenesis across species. Genetic, biochemical, and histological analyses of this mutant and a comparison to a second, similar locus reveal that Bmp1a is critically required for mature-collagen generation, downstream of osteoblast maturation, in bone. We thus define the molecular and cellular bases of BMP1-dependent osteogenesis and show the importance of this protein for bone formation and stability.